EFFECTIVENESS OF EDUCATIONAL GAME MEDIA TO IMPROVE RESULTS LEARNING PANCASILA EDUCATION FOR GRADE I STUDENTS STATE ELEMENTARY SCHOOL 48 BANDA ACEH - Safrina Nura (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to test the effectiveness of educational game media to improve student learning outcomes in Pancasila education lessons for grade I students at Elementary School 48 Banda Aceh. This study is classified into quantitative research with a pre-experimental design method (pre-experiments design) type one group pre-test and post-test design with treatment given to only one experimental group without using a control group. This study was conducted at Elementary School 48 Banda Aceh. Data collection techniques in this study involved three main methods of testing, and documentation. The data analysis method in this study used SPSS (Statistical Package for the Social Sciences) software version 21. The analysis included validity, reliability, and homogeneity tests. The normality test was carried out using the One-Sample Kolmogorov-Smirnov Test. The analysis included the calculation of Effect Size and N-Gain, as well as hypothesis testing using the t-test. Based on the results of the study and data analysis, it can be concluded that educational game media is effective in improving student learning outcomes in the material on Pancasila symbols and principles. This can be seen from the comparison of pre-test and post-test scores on student learning outcomes, where the pre-test score of 49.63 increased significantly to 84.63 in the post-test. The results of the hypothesis test show that the t-count value is greater than the t-table, which is (2.439> 1.670). So the null hypothesis (H₀) is rejected, which means that the use of educational game media is effective in improving student learning outcomes, with an effect size value of 0.4 with a medium category at a significance level of α = 0.05.